Decoding synpolydactyly the genetic landscape of hoxd13 and the hox gene family" A comprehensive review" (Zoo Botanica, 2025)
Congenital limb malformations are among the most prevalent developmental abnormalities, occurring in approximately one in every 500 live births. These defects are frequently linked to genetic disruptions within the HOX gene family, which plays a pivotal role in embryonic limb patterning. This review comprehensively examines the genetic and molecular basis of synpolydactyly (SPD) a hereditary limb deformity characterized by fusion and duplication of digits focusing on the HOXD13 gene and its association with other HOX genes. Mutations in HOXD13, including polyalanine tract expansions, missense, nonsense, and frameshift mutations, have been identified as major contributors to SPD and related limb malformations. Furthermore, the functional interplay between HOXD13 and other HOX genes (HOXA1, HOXA2, HOXA11, HOXA13, HOXB1, and HOXB13) underlies a spectrum of genetic syndromes affecting limb and organ development. The review highlights the genotype–phenotype correlations, molecular mechanisms of HOXD13 mutations, and their broader implications in developmental and pathological contexts, including genitourinary and oncogenic disorders. Understanding the complex regulation of HOXD13 and its paralogues provide critical insight into congenital limb anomalies and offers a framework for genetic counseling, diagnosis, and potential therapeutic strategies.
Keywords: Synpolydactyly; Hox gene; mutation; polyalanine; duplication